Multiple Comparisons of the Efficacy and Safety for Seven Treatments in Tibia Shaft Fracture Patients - Li, Haibo; Yu, Dapeng; Wu, Shaobin; Zhang, Yihang; Ma, Liang (Frontiers in Pharmacology, 2019)
Background: Tibia shaft fracture is the most common long bone fractures, with two general types, open fracture and close fracture. However, there is no universally accepted guideline suggesting which treatment to use under certain circumstances. Therefore, a comprehensive network meta-analysis (NMA) is demanded to summarize existing studies and provide a more credible data-based medical guideline. Methods: Available literatures were identified by searching the internet medical database with relevant key terms. For studies meeting the inclusion and exclusion criteria, baseline, intervention and outcomes of each treatment were extracted. Comparative connection of studies was demonstrated by net plots. Continuous variables and binary variables were reported as mean difference (MD) and odds ratio (OR) with 95% credible interval (CrI), respectively. The comparison of direct and indirect outcome and their P-value were listed in the node-splitting table. Treatments for each endpoint were ranked by their surface under the cumulative ranking curve (SUCRA) value. Heat plot was performed to illustrate the contribution of raw data and the inconsistency between direct and indirect comparison. Results: According to the search strategy, 697 publications were identified and 25 records were kept, with 3032 patients of tibia shaft fracture involved. And seven common surgical or non-surgical treatments, including reamed intramedullary nailing (RIN), un-reamed intramedullary nailing (UIN), minimally reamed intramedullary nailing (MIN), ender nailing (EN), external fixation (EF), plate and cast, were compared, in terms of time to union, reoperation, nonunion, malunion, infection and implant failure. Plate performed relatively better for time to union, while cast might be the best choice in close cases for reducing the risks of reoperation, nonunion, malunion and infection. For preventing implant failure, EN seemed to be better. Conclusion: Cast might have the highest probability to be the optimal choice for tibia shaft fracture in close cases, and reamed intramedullary nailing ranked second.